PENGEMBANGAN SPOT FOTO KREATIF MELALUI PEMBUATAN FRAME FOTO DI WISATA LPHD BATU MENTAS - Eko Pratama; Astrid Juliyanti; Dwi Fajaria; Putrianti; Ratri Kusumadita; Gea Cantika; Syandhu Dea Fermanda; Ayu Nuratika; Febrianus Jerabun; Rakha Piadika (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
The UNMUH BABEL Community Service Program (KKN) at the Batu Mentas Village Community Service Center (LPHD) is located in Badau Village, Belitung Regency, which boasts beautiful tropical forests, clear streams, large rock formations, and a camping area. However, visual facilities, such as photo spots, are still limited. This community service activity aimed to create a creative, triangular photo spot made from bamboo and wood that blends seamlessly with the surrounding environment. The method used was a participatory approach, involving tourism managers in every stage, from site identification and design planning to material processing, to installation and evaluation. The results of the activity showed that the photo spot received a positive response from tourism managers and has the potential to become an effective promotional tool through social media posts. This innovation is expected to increase tourist visits, strengthen the destination's image as a sustainable ecotourism destination, and provide economic benefits to the local community.